2020
DOI: 10.1002/cpp.2426
|View full text |Cite
|
Sign up to set email alerts
|

“Will you treat me? I'm suicidal!” The effect of patient gender, suicidal severity, and therapist characteristics on the therapist's likelihood to treat a hypothetical suicidal patient

Abstract: The purpose of our study was to broaden the understanding regarding mental health professionals' willingness to treat and likeliness to refer suicidal patients to other professionals. More specifically, our aim was to examine the effect of the patient's gender and suicidal severity, as well as the mental health professionals' personal and professional characteristics, on the willingness to treat and likeliness to refer. A total of 331 mental health professionals were randomly exposed to one of four case descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Additionally, given the established understanding of adult learning as predominantly problem‐focused (Knowles, 1984), the current findings will ideally inform dedicated training for therapists in engaging and motivating male clients, helping them to identify and understand their emotional experiences, and responding therapeutically to interpersonal difficulty while clearly asserting one's boundaries. These findings are a call to action derived directly from the therapists themselves, dovetailing existing research highlighting that some therapists have been found to have poorer clinical outcomes specifically with male clients compared to others (Owen et al, 2009) and that many therapists feel less competent and willing to work with suicidal men than women (Almaliah‐Rauscher et al, 2020). Improving therapists' understanding of masculine socialization as an underpinning factor in men's presentation to therapy and the manifestation of their distress could have far‐reaching impacts in helping therapists achieve positive outcomes with their male clients.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, given the established understanding of adult learning as predominantly problem‐focused (Knowles, 1984), the current findings will ideally inform dedicated training for therapists in engaging and motivating male clients, helping them to identify and understand their emotional experiences, and responding therapeutically to interpersonal difficulty while clearly asserting one's boundaries. These findings are a call to action derived directly from the therapists themselves, dovetailing existing research highlighting that some therapists have been found to have poorer clinical outcomes specifically with male clients compared to others (Owen et al, 2009) and that many therapists feel less competent and willing to work with suicidal men than women (Almaliah‐Rauscher et al, 2020). Improving therapists' understanding of masculine socialization as an underpinning factor in men's presentation to therapy and the manifestation of their distress could have far‐reaching impacts in helping therapists achieve positive outcomes with their male clients.…”
Section: Discussionmentioning
confidence: 58%
“…Without appropriate awareness and training, therapists may be unaware of their beliefs and biases about men’s mental health and become complicit in reinforcing rigid and unhelpful stereotypes about male emotionality or help-seeking (Seidler, Rice, Dhillon, et al, 2019). For example, Almaliah-Rauscher et al (2020) highlighted that therapists are often less confident and unwilling to treat male clients with complex needs such as suicidality than they are female clients—a bias that may problematize the extent to which therapists can provide an effective service, or referral pathway for men, potentially explaining the observed association between lack of therapy engagement and dropout. Conversely, men identifying more strongly with traditional masculinity were less likely to have dropped out due to a lack of therapist–client connection.…”
Section: Discussionmentioning
confidence: 99%
“…These potential biases likely extend to practitioners' competence and confidence in treating men presenting with suicidality. As an example, practitioners report a lower willingness to treat suicidal men relative to suicidal women (Almaliah-Rauscher et al, 2020). There is also evidence of practitioner subgroup effects, particularly in relation to gender.…”
mentioning
confidence: 99%